2021
DOI: 10.1016/j.jcrc.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Single versus multiple doses of Tocilizumab in critically ill patients with coronavirus disease 2019 (COVID-19): A two-center, retrospective cohort study

Abstract: Purpose To evaluate the effectiveness and safety of the optimal tocilizumab dosing regimen. Methods A two-center, retrospective cohort study, for COVID19 critically ill patients admitted to the intensive care units (ICUs). We included critically ill patients aged 18 years or older who received tocilizumab during ICU stay. Patients were divided into two groups based on the number of the received tocilizumab doses. The primary outcome was the in-hospital and 30-day mortal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…The 148 included studies were published between December, 2019, and May, 2021. 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , ...…”
Section: Resultsmentioning
confidence: 99%
“…However, this was limited by the study design and the short follow-up period to confirm the association between tocilizumab and the higher rate of secondary infections [ 29 ]. Another recently published retrospective cohort study conducted on critically ill patients with COVID-19 found that multiple doses of tocilizumab were associated with higher odds of pneumonia than a single dose [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study done by Sulaiman et al found no significant mortality benefit when assessing single-dose versus multiple-dose arm COVID-19 patients in Saudi Arabia. 18 The novelty of the present study lies in making a decision support system in the name of HTC, assessing the rational utilization of costly drugs with uncertain benefits. To the best of our knowledge, there exists no study comparing the dead versus survived COVID-19 pneumonia patients receiving tocilizumab.…”
Section: Resultsmentioning
confidence: 99%